INTEGRASI SOSIAL UMAT BERAGAMA DALAM PENYELESAIAN KONFLIK BERNUANSA AGAMA DI KECAMATAN KEPIL WONOSOBO - Achmad Rosidi (Harmoni, 2016)
This article describes about Wonosobo community who have customs and traditions as the Javanese society which are heavely attached to local genius. The characteristics of the Javanese society are friendly as the eastern people who have the same background as a nation who loves peace. The process of social integration among religious people in Kepil, Wonosobo becomes a prototype of problem resolution on interreligious relationship to prevent any potential conflict that can occur. Aspects that can cause conflict come from external force can be minimized by religious figures who are assigned to be member of harmony forum. The problem lying in the society is about religious conversion that are massively happening from Buddhism to Islam at the same time. This study used qualitative approach by collecting data through observation, interview, document exploration and these data were analized through triangulation method. In conclusion, the process of social integration in Wonosobo society can overcome negative issues that can generate disintegration.